Public values theory: What is missing? - Fukumoto, Eriko; Bozeman, Barry (American Review of Public Administration)
Scholars of public value and public values have sought to develop theory by defining, identifying, classifying, and measuring the values, some of which articulate theoretical problems and prescriptions such as values pluralism and the scope of the concept itself. Despite the richness of both theoretical and empirical developments, scholars of public values recognize the fragmentation of related research and seek to re-think and re-organize studies of public values. Considering these works, this current study is an effort to articulate and synthesize the issues in the research approach in public values. Our study provides an overview of public values theory and research with an emphasis on major developments related to value classification schemes and analytical frameworks. The study examines three problems in theory research of public values, namely, the identification problem, motivation problem, and instrument problem. After describing the detailed problems with some examples, the authors suggest approaches to the improvement of theory and research in public values, emphasizing the utility of longitudinal and historical studies. - Reproduced.